INDICES OF BODY COMPOSITION RELATED TO PHYSICAL FITNESS FOR THE HEALTH OF ADULT WOMEN FROM THE WEST ZONE OF RIO DE JANEIRO. (Fiep Bulletin - online, 2011)
Body composition is considered a component of physical fitness for the health, because of the relations between body fat and changes in the level of physical fitness and health (ACSM, 2007). The research objective was to compare and correlate measures estimated of body fat percentage (%BF) by body mass index (BMI) to measures with waist circumference (WC), waist hip ratio (WHR) and BMI. The sample consisted of 83 adult women residents of the West Zone of Rio de Janeiro in between of 27.59 ± 8.86 years old. To determine the distribution of body fat equations were used to estimate %BF by BMI and age, as proposed by Deurenberg et al. (1991) (%BFD) and Lean et al. (1996) (%BFL). We used the formula weight/height2 for calculating the BMI. The WC and WHR were used according to the references of WHO (1998). BMI, WC and WHR values were considered normal however %BFD and %BFL featured health risk, with significant differences between these two measures using the Wilcoxon test. The Pearson correlation coefficient(r) was strong positive correlation between BMI and %BFL (r= 0.939) and BFD% with BMI (r= 0.950), between WC with %BFL and %BFD the correlation was moderate, but among WHR with %BFD and %BFL the correlation was weak. As it was seen from the equations %BFD and %BFL had a strong positive correlation with BMI precisely, allowing the use of them, along with BMI to determine demographics, body composition and health risk. However the weakest levels in correlation among WHR and WC to %BFD and %BFL, do not allow us to propose the use of these equations with these variables to check the above conditions.
Keywords: Body composition; Body fat; Body mass index